Using Chitosan-Coated Polymeric Nanoparticles-Thermosensitive Hydrogels in association with Limonene as Skin Drug Delivery Strategy - Campos, Estefânia V. R.; Proença, Patrícia L. F. [UNESP]; Costa, Tais G. da; Lima, Renata de; Fraceto, Leonardo F. [UNESP]; Araujo, Daniele R. de (Wiley, 2022)
Topical delivery of local anesthetics (LAs) is commonly used to decrease painful sensations, block pain throughout procedures, and alleviate pain after surgery. Dermal and/or transdermal delivery of LAs has other advantages, such as sustained drug delivery and decreased systemic adverse effects. This study reports the development of poly(D,L-lactide-co-glycolide) (PLGA) nanoparticles coated with chitosan for the sustained release and topicality of benzocaine (BZC) and topical delivery. BZC PLGA nanoparticles or nonencapsulated drugs were further incorporated into Poloxamer hydrogels (Pluronic™ F-127). The nanoparticles showed a mean diameter of 380±4 nm, positive zeta potential after coating with chitosan (23.3±1.7 mV), and high encapsulation efficiency (96.7±0.02%). Cellular viability greater than 70% for both fibroblasts and keratinocytes was observed after treatment with nanoparticles, which is in accordance with the preconized guidelines for biomedical devices and delivery systems. Both the nanoparticles and hydrogels were able to modulate BZC delivery and increase drug permeation when compared to the nonencapsulated drug. Furthermore, the incorporation of limonene into hydrogels containing BZC-loaded nanoparticles increased the BZC permeation rates. Non-Newtonian and pseudoplastic behaviors were observed for all hydrogel nanoformulations with or without nanoparticles. These results demonstrate that the hydrogel-nanoparticle hybrids could be a promising delivery system for prolonged local anesthetic therapy.